Starters vs. non-starters differences in vertical jump force-time metrics in female professional volleyball players - Cabarkapa, Damjana V.; Cabarkapa, Dimitrije; Fry, Andrew C. (Frontiers in Sports and Active Living, 2024)
As one of the fundamental volleyball skills, countermovement vertical jump (CMJ) has been commonly implemented in the applied sports setting as a non-invasive and time-efficient assessment of athletes' lower-body neuromuscular function. The purpose of the present study was to examine the differences in CMJ characteristics between starters and non-starters within a cohort of professional female volleyball players. Nineteen athletes competing in one of the top European leagues volunteered to participate in the present investigation. Following the completion of a warm-up protocol, each athlete performed three maximal-effort CMJs with no arm swing while standing on a uni-axial force plate system sampling at 1000 Hz. The following force-time metrics were used for performance analysis purposes: braking phase duration and impulse, eccentric and concentric duration, mean and peak force and power, contraction time, jump height, and reactive strength index-modified. Mann-Whitney U and independent t-tests revealed no statistically significant differences (p>0.05) during both eccentric and concentric phases of CMJ between the players included in the starting lineup (n=9) and their substitutions (n=10), with the effect sizes being small to moderate in magnitude (g=0.053 -0.683). While further research is warranted on this topic, these results suggest that securing a position in a starting lineup at the professional level of volleyball play may be more contingent on the player's ability to proficiently execute sport-specific skills (e.g., blocking, attacking), rather than the performance on the CMJ assessment, considering that the observed values for both groups fall within the desired ranges for this specific population of athletes.